Comparative Analysis of Social Security Systems in High HDI Nations: Extractable Features for U.S. Reform - Lee, Josephine (Advances in Social Sciences Research Journal, 2025)
This research examines social security systems across nations ranking highest on the Human Development Index, analyzing structural elements, funding mechanisms, and benefit designs that contribute to their effectiveness and sustainability. Through comparative institutional analysis of Norway, Switzerland, Iceland, Hong Kong, Denmark, and Sweden, this study identifies transferable features that could potentially address the United States’ impending social security crisis, where trust fund reserves are projected for depletion by 2034, potentially triggering benefit reductions of approximately 23%. The analysis reveals that successful systems consistently incorporate multi-pillar frameworks distributing responsibility across public, occupational, and private domains; implement diversified funding structures extending beyond traditional payroll contributions; establish flexible retirement provisions facilitating personalized work-retirement transitions; and deploy automatic adjustment mechanisms that enhance sustainability without continuous political intervention. Despite the presence of these common features, contextual factors including distinctive labor market structures, cultural attitudes toward taxation and redistribution, and demographic profiles, significantly constrain direct policy transfer. Nevertheless, the research identifies adaptation pathways, including strengthening mandatory occupational coverage, implementing flexible retirement mechanisms, diversifying revenue sources, and establishing automatic stabilizers, that could feasibly address critical vulnerabilities in the U.S. system while acknowledging institutional and political constraints. The study concludes that effective reform requires systemic rather than parametric adjustments, emphasizing the importance of incremental implementation sequencing, strategically framed policy narratives, and careful consideration of distributional impacts across diverse population segments.